2020
DOI: 10.1523/jneurosci.1680-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Stimulation of an Orbitofrontal Network Disrupts Decisions Based on Inferred, Not Experienced Outcomes

Abstract: When direct experience is unavailable, animals and humans can imagine or infer the future to guide decisions. Behavior based on direct experience versus inference may recruit partially distinct brain circuits. In rodents, the orbitofrontal cortex (OFC) contains neural signatures of inferred outcomes, and OFC is necessary for behavior that requires inference but not for responding driven by direct experience. In humans, OFC activity is also correlated with inferred outcomes, but it is unclear whether OFC activi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Evidence that the lateral OFC mediates the effect of trait representations on social decision-making connects to a large body of evidence in humans and other species that the OFC contributes to decision-making that is guided by inference or imagination of outcomes. Previous studies used paradigms such as outcome devaluation or preconditioning to demonstrate that the OFC (in particular, the lateral OFC) is necessary for inference-based decision-making in rats ( 43 , 44 ), monkeys ( 45 , 46 ), and humans ( 47 49 ). Furthermore, recent neuroimaging and electrophysiological studies revealed that the OFC represents latent features of the environment, such as the hidden state of the present trial in sequential or learning tasks, that are not directly observable but are critical for outcome prediction ( 29 , 30 , 50 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that the lateral OFC mediates the effect of trait representations on social decision-making connects to a large body of evidence in humans and other species that the OFC contributes to decision-making that is guided by inference or imagination of outcomes. Previous studies used paradigms such as outcome devaluation or preconditioning to demonstrate that the OFC (in particular, the lateral OFC) is necessary for inference-based decision-making in rats ( 43 , 44 ), monkeys ( 45 , 46 ), and humans ( 47 49 ). Furthermore, recent neuroimaging and electrophysiological studies revealed that the OFC represents latent features of the environment, such as the hidden state of the present trial in sequential or learning tasks, that are not directly observable but are critical for outcome prediction ( 29 , 30 , 50 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pure odors and odor mixtures were presented to participants via a computer-controlled olfactometer at a steady flow rate of 3.2 L/min, as in our previous studies [ 16 , 42 , 67 ]. The olfactometer included 2 mass flow controllers (Alicat Scientific, Tucscon, Arizona, USA) that operated independently, so pure odors could be diluted with odorless air, and food and nonfood food odors could be combined to form custom mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…Reducing activity in OFC seems counterproductive at first glance: the OFC is responsible for the very behaviors that are deficient in disorders of compulsivity. In addition, cTBS to the right dlPFC, including areas selected based on OFC connectivity, has been found to reduce—not increase—model-based planning and use of learned cue-cue associations in nonclinical populations (Smittenaar et al, 2013; Wang et al, 2020). Disorders of compulsivity are linked to maladaptive behavior in interconnected cortico-striatal-thalamic loops, not just OFC activity.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found good test–retest reliability and temporal stability of model-based planning in people with elevated compulsivity symptoms (Brown et al, 2020) and that OCD symptom improvement after exposure and response prevention did not significantly change model-based planning (Wheaton et al, 2019), suggesting that behavioral measures of compulsivity are stable and persistent. However, acute neural circuit modification, via transcranial magnetic stimulation, can rapidly reduce use of model-based planning, as measured by behavioral indices (Smittenaar et al, 2013; Wang et al, 2020). In addition, although several behavioral tasks correlate with compulsive behaviors in separate investigations, little work has investigated whether measures from different tasks are measuring the same construct.…”
mentioning
confidence: 99%